STRATEGI PENDAMPING SANTRI DALAM PENANAMAN KARAKTER SOSIAL - Arie Muhammad D; Hamidah, Tutik; Zuhroh, Ni'matuz (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Social character is one of the traits that educators must instill in students as a means of self-adjustment in Islamic boarding schools. Mentors, acting as middle managers, play an active role in instilling social character in students at Sabilurrosyad Putra Gasek Islamic Boarding School in Malang. The aim of this research is to reveal the strategies employed by mentors in instilling social character in students. The research methodology used is descriptive qualitative through interviews, observations, and documentation. The results of this study indicate that mentors employ strategies to instill social character in students through a series of rules, learning activities, and guidance that emphasize providing guidance and advice, followed by setting direct examples in daily activities.